Bioinformatics and expression analysis of finTRIM genes in grass carp, Ctenopharyngodon idella. Issue 66 (July 2017) - Luo, Kai; Li, Youshen; Ai, Kete; Xia, Lihai; Zhang, Jinxiong; Hu, Wei; Gao, Weihua; Guo, Liwei; Qi, Zhitao; Yuan, Hanwen; Xu, Qiaoqing
Abstract: The tripartite motifs (TRIMs) constitute a large family of proteins containing a Really Interesting New Gene (RING) domain, a B-box domain and coiled-coil region followed by different C-terminal domains. TRIM proteins play multiple roles in various cellular processes, including cell growth, differentiation, apoptosis and antiviral immunity. Fish novel large multigene TRIM genes ( finTRIM/ftr ) appear only in teleosts and play a vital role in antiviral responses. Phylogenetic analysis revealed the existence of different subsets of novel fish TRIM 14 genes ( finTRIM14 / ftr14 ), ftr51, ftr67, ftr72, ftr82, ftr83, and ftr99 in grass carp ( Ctenopharyngodon idella ), suggesting lineage-specific diversification events. Therefore, the number of finTRIM genes varies greatly among species. The ftr genes in grass carp, which are closely related to zebrafish and possess various evolutionary branches, have evolved faster than human TRIMs. The predicted protein domains were almost identical RING zinc finger domains, with the exception of ftr72, the B-box domain (excluding ftr67, ftr82, ftr83 ), and the B30.2 domain, which evolved under positive selection (with the exception of ftr67, and ftr72 ). The genes were predominantly expressed in the spleen, gill and head kidney. These findings indicate that the ftr genes in grass carp are involved diverse cellular processes, including innate immune responses. Highlights: The manuscript first reported the sequences of finTRIM in grass carp. The sequence alignments, phylogenetic tree analysis, conserved domain analysis and exon/intron organization of finTRIM was conducted. The expression pattern of finTRIM in different tissues was analysed.